The European Union - a ‘Sui Generis’ International Diplomatic Actor: Challenges Posed to the International Diplomatic Law - Ruxandra Laura Boşilcă (Romanian Journal of European Affairs)
It has often been argued that the European Union has a sui generis status by being less than a nation-state, but more than an international organization, which is also reflected in its conduct of diplomatic relations with third states and international organizations. Since its inception, the European Union has managed to set a wide bi- and multilateral diplomatic network – which is subject to the provisions of the 1961 Vienna Convention on Diplomatic Relations (VCDR). This paper`s purpose is to analyze some of the main challenges posed to the international diplomatic law by the EU`s emergence on the diplomatic scene, in the light of the significant transformations brought by the Lisbon Treaty.